Islamic Corporate Social Responsibility (ICSR) disclosure and Islamic Banks (IBs) performance: The application of stakeholder theory from Islamic perspective - Ichsan Setiyo Budi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
This study aims to examine the effect of ICSR disclosure on the performance of IBs in Indonesia. Disclosures are prepared based on AAOIFI standards and previous researches then formed a disclosure index, while the performance of IBs is compiled from financial performances: ROA, ROE, and productivity performances which are formed into variables are formed by factor analysis. The samples of this research are 12 IBs from 2008 until 2019. Several IBs that had not yet been established in 2008 had been observed since the establishment of the banks until 2019, from this, it is obtained 121 observations. The test results show that all indicators of ICSR disclosure consisting of eight indicators: sharia compliance, ethical behavior, management, human resources, environment, social activities, products and services, research and development, and training have a positive effect on the performance of IBs. This provides an understanding that all of the disclosure indicators provide a good image or reputation to the public, thereby generating trust and in the long-term improving the performance of IBs.